Probiotic Characterization of Lactic Acid Bacteria from Donkey Feces in China - Yanqiu Wu; Shousong Yue; Jinhui Yu; Fei Bian; Gao Chen; Yan Zhang (Animals)
Probiotics are beneficial to humans and animals and often used for regulating immunity, intestinal microbiota balance, and animal growth performance. Donkey husbandry has boomed in China in recent years and there is an urgent need for probiotics effective for improving donkey health. However, studies on potential probiotic strains isolated from donkeys are scarce. This project aimed to screen LAB strains from donkey feces, detect their antimicrobial activity and evaluate their probiotic characteristics in vitro. Thirteen LAB isolates showed different degrees of antimicrobial activity against four indicator bacteria: three common pathogens (Escherichia coli, Staphylococcus aureus, and Salmonella typhimurium) and one pathogen restricted to equines (Salmonella. abortus equi), eight of which could inhibit all four pathogens. Seven isolates showed higher tolerance to low pH and bile salts, with >50% and >60% survival rates, respectively. Five of them had more than 50% survival rate to artificial gastric and intestinal fluids. Only three isolates possessed good properties, with >40% auto-aggregation, >40% hydrophobicity, and high co-aggregation with the indicator pathogens. An L9 isolate, identified as Ligilactobacillus salivarius, was sensitive to most antibiotics tested. Overall, these results indicate that the L. salivarius L9 isolate meets the requirements of the probiotics selection criteria in vitro and can potentially be developed as a probiotic for donkeys.